2007
DOI: 10.1038/sj.bjc.6604109
|View full text |Cite
|
Sign up to set email alerts
|

Risk of testicular germ-cell tumours in relation to childhood physical activity

Abstract: The US Servicemen's Testicular Tumor Environmental and Endocrine Determinants (STEED) case -control study of testicular germcell tumours (TGCTs) enrolled participants and their mothers in 2002 -2005. Hours of sports or vigorous childhood physical activity per week were ascertained for three time periods; 1st -5th grades, 6th -8th grades and 9th -12th grades. Son-and mother-reports were analysed separately and included 539 control son -mother pairs and 499 case son -mother pairs. Odds ratios and 95% confidence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 18 publications
(24 reference statements)
0
29
0
Order By: Relevance
“…3.5). Four studies (Cook et al 2008;Dosemeci et al 1993;Littman et al 2009;Srivastava and Kreiger 2000) reported a null association and two studies found a statistically nonsignificant positive relation between physical activity and testicular cancer (Paffenbarger et al 1987;Thune and Lund 1994). One study noted a statistically nonsignificant inverse association between time spent sitting and testicular cancer (Dosemeci et al 1993).…”
Section: Overall Association Between Physical Activity and Testicularmentioning
confidence: 91%
See 4 more Smart Citations
“…3.5). Four studies (Cook et al 2008;Dosemeci et al 1993;Littman et al 2009;Srivastava and Kreiger 2000) reported a null association and two studies found a statistically nonsignificant positive relation between physical activity and testicular cancer (Paffenbarger et al 1987;Thune and Lund 1994). One study noted a statistically nonsignificant inverse association between time spent sitting and testicular cancer (Dosemeci et al 1993).…”
Section: Overall Association Between Physical Activity and Testicularmentioning
confidence: 91%
“…Testicular Cancer Study Group 1994) of the nine studies (Brownson et al 1991;Cook et al 2008;Dosemeci et al 1993;Gallagher et al 1995;Littman et al 2009;Paffenbarger et al 1987;Srivastava and Kreiger 2000;Thune and Lund, 1994;U.K. Testicular Cancer Study Group 1994) that examined physical activity in relation to testicular cancer observed a statistically inverse association between a measure of physical activity and testicular cancer (Fig.…”
Section: Overall Association Between Physical Activity and Testicularmentioning
confidence: 93%
See 3 more Smart Citations